Mutation of MUC16 Is Associated With Tumor Mutational Burden and Lymph Node Metastasis in Patients With Gastric Cancer - Zhang, Fengxiang; Li, Xianzhe; Chen, Huaxian; Guo, Jianping; Xiong, Zhizhong; Yin, Shi; Jin, Longyang; Chen, Xijie; Luo, Dandong; Tang, Haijie; Mao, Chaobin; Lian, Lei (Frontiers in Medicine, 2022)
Background: Lymph node metastasis (LNM) is a critical factor in determining the prognosis of gastric cancer (GC), but its underlying mechanism remains unclear. The tumor mutational burden (TMB) has recently been recognized as a biomarker for predicting prognosis and response to immune checkpoint inhibitors, while mucin 16, cell surface associated (MUC16) is frequently mutated in GC. This study explored whether MUC16 mutation status is associated with TMB, LNM, and prognosis in patients with GC. Methods: Somatic mutation data were downloaded from three GC cohorts. TMB values were calculated and associations between the TMB and clinical characteristics were analyzed. The mutational landscapes of these three GC cohorts were individually explored and visualized using waterfall diagrams. Univariate logistic regression and Kaplan-Meier survival analysis were performed to screen for mutated genes associated with LNM and overall survival (OS). Associations between MUC16 mutations and TMB, microsatellite instability (MSI), LNM, and tumor microenvironment signatures were explored. Results: TMB was associated with LNM and OS in patients with GC. Analyzing the three GC cohorts (The Cancer Genome Atlas-Stomach Adenocarcinoma, International Cancer Genome Consortium [ICGC]-China, and ICGC-Japan) revealed that MUC16 was one of the most frequently mutated genes in patients with GC. MUC16 mutations were associated with better prognosis, including lower LNM rates and improved OS rates. In addition, MUC16 mutation status was associated with TMB and MSI statuses. Fifteen upregulated and 222 downregulated genes were identified in patients with MUC16 mutations, compared to in those in patients with wild-type MUC16. An altered tumor microenvironment signature was also identified in GC samples with MUC16 mutations; it was characterized by significantly decreased infiltration regarding stromal cells, CD4+ T cells, and macrophages. Conclusion: MUC16 mutation status was associated with TMB, microsatellite status, LNM, and survival in patients with GC. These findings may provide new insights into the mechanism of LNM and could act as a signpost for prognostic predictions and immunotherapy guidance for patients with GC.